ANALISIS KESIAPAN MAHASISWA PG-PAUD UNIVERSITAS TERBUKA MALANG DALAM PEMBELAJARAN BERBASIS E-LEARNING SEBAGAI DAMPAK PANDEMI VIRUS COVID 19 - Esti Kurniawati Mahardika; Dhita Paranita Ningtyas (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2020)
During the pandemic caused by Covid-19 which occurred in Indonesia had a major impact on various sectors, one of which was the tertiary education sector. UT in Malang felt the impact of learning carried out with E-Learning. The research subjects were the 4th and 6th semester students of PG-PAUD Universitas Terbuka, as many as 100 students participated. Descriptive qualitative research methods, survey data collection and interviews with the results of the description of the results stating that PGPAUD UT students were not ready to do full E-Learning during the covid-19 pandemic. However, learning must be carried out and effective learning methods are needed to maximize the delivery of material.